Cluster-Management as a Technology for Increasing the Efficiency of Territory Resource Exploitation in a Region - Gureva, Maria A.; Litvinenko, Inna L.; Shichiyakh, Rustem A.; Kolpak, Eugeny P.; Novoselova, Natalya N. (International Journal of Economics and Financial Issues, 2016)
The topicality of cluster formation and their management is determined by the general ways of economic upswing at the present stage of developing Russia. It also lies in developing a partnership with the state, economy and science. A cluster serves as a paradigm under which the general output, beginning with its development, initial production work and ending with its sale, follows in the single chain order. In the modern market environment of functioning and development the national and regional economy everything is largely caused by the regularities of the global processes, which are determined as both the new world economic ties formation and the specific status definition of a certain state, region and enterprise in the structure of world economy. The economic integration can be considered as one of the main components of globalization. Any high-organized system seeks for strengthening its integrity objectively, for there are no specific goal, structuring and hierarchical pattern, distinguishing the system from the simple set of any things and phenomena between its forming elements when consolidating the ties and relations. Consolidating economic entities, strengthening their interactions and developing the economic and social relations between them are defined as an economic integration (the word “integer” from Latin means “whole”, “unitary”). Keywords: cluster, cluster management, territorial production cluster (TPC), globalization, innovations, technological park JEL Classifications: P25, P28, R1, R12